Comparison of relapse rates in Behçet's disease with venous involvement on different doses of azathioprine therapy, a retrospective observational study. (26th February 2021) - Girgin, Sinem; Yurumez, Seda; Omma, Ahmet; Celik, Selda; Cemal Icacan, Ozan; Bes, Cemal; Alpay‐Kanitez, Nilufer
Abstract: Aim: The aim of this study was to investigate relapse rates in azathioprine (AZA) maintenance therapy at different doses in Behçet's disease (BD) with venous involvement. Method: Clinical records of patients who met the diagnostic criteria of International Study Group (ISG) for BD, were diagnosed with venous involvement of BD for at least 6 months and sustained clinical remission with AZA for at least 3 months were analyzed retrospectively. The analysis cohort was divided into 2 groups based on AZA dose (Group A: ≥ 2 mg/kg/d and Group B: <2 mg/kg/d). Relapse was defined as requiring another antirheumatic/immunosuppressive drug or more than dose of 10 mg/d of prednisolone. Results: Of 78 patients who were included into the study, there was no significant difference between the 2 groups in terms of age, gender and clinical characteristics. Mean relapse‐free survival time was found to be higher in group A compared to group B (111.6 ± 11.2, 95% CI 89.5 ± 133.8 versus 51.5 ± 6.1, 95% CI 39.5 ± 63.4 months). Conclusion: Relapse‐free survival rate was less in the group receiving low‐dose AZA and shows the importance of effective dose of AZA in maintenance therapy.